Concomitance of Familial Mediterranean Fever and Gitelman syndrome in an adolescent - Bahriye Atmış; Rabia Miray Kışla-Ekinci; Engin Melek; Atıl Bişgin; Mustafa Yılmaz; Ali Anarat; Aysun Karabay-Bayazıt (The Turkish Journal of Pediatrics)
Gitelman syndrome is a renal tubular salt-wasting disorder characterized by hypokalemic metabolic alkalosis with hypomagnesemia and hypocalciuria. Patients occasionally have symptoms in childhood, while diagnosis is often in adulthood. It is inherited by an autosomal recessive manner through SLC12A3 gene mutations. Familial Mediterranean Fever (FMF) is the most common autoinflammatory disorder, inherited by an autosomal recessive manner and characterized by recurrent fever and pleuritis, peritonitis, and synovitis. Mutations in MEditerrenean FeVer (MEFV) gene, coding pyrin protein are responsible for FMF. Both MEFV and SCL12A3 genes were located on chromosome 16. A 9-year-old boy was admitted to our department because of recurrent abdominal pain, fever, joint pain and swelling since he was three years old. He was diagnosed as FMF and MEFV gene sequencing revealed homozygous M694V (c.2080A > G) mutation. At the age of 14 years, polyuria, polydipsia, hypokalemia and mild hypomagnesemia had occurred. Patient was successfully treated with oral supplementation of potassium and magnesium along with colchicine. Molecular genetic analysis including SCL12A3 gene sequencing revealed homozygote IVS4-16G > A (c.602-16G > A) intronic splicing site mutation.